Hubungan Literasi Digital Perempuan Dalam Media Online Untuk Antisipasi Fenomena Kekerasan Dalam Rumah Tangga (Kdrt) - Rekno Sulandjari; Retno Djohar Juliani; Agustien Zulaidah; Fitri Darayani (Universitas 17 Agustus 1945, 2023)
The era of media convergence makes life easier with the adoption of knowledge through online media. In addition to obtaining various information, online media also has a significant contribution in changing the behavior of its users in responding to a phenomenon in everyday life. Especially women whose roles in this era of media convergence are increasingly complex. He not only acts as the head of the household, but sometimes his role is also as the head of the family to make a basic living or just as a breadwinner to support household life. In addition, responding to the phenomenon of domestic violence that is often found in the news, makes women try to also contribute to maintaining the integrity of their household by minimizing this phenomenon in their family. Various efforts have been made, one of which is to increase understanding of domestic violence itself. Through digital literacy, it is hoped that apart from having their own understanding of domestic violence, they can also share this information with their own environment and family. So you can anticipate it if it hasn't happened yet, and minimize it if it does happen without realizing it.The phenomenon of women in the category of always doing digital literacy in using online media is 66.93%. This is almost entirely dominated by women empowerment activists in RW XIII Pucang Gading Housing. Where besides having activities outside the home as an employee, educator, NGO member, businessman, doctor and so on, they are also very responsive to the importance of gender equality in running a household life. While the results of research to adopt knowledge and understanding of digital literacy regarding steps that can be anticipated to minimize the phenomenon of domestic violence obtained results of 61.66%. One of them is that women must also be economically independent and have positive activities in order to increase welfare for the family. Thus, respect arises from the partner to put more effort into efforts to achieve in activities to seek economic sufficiency for the needs of the family which is increasing from time to time. In this study, the final results showed that there was a positive relationship between online digital media literacy and the phenomenon of domestic violence by 58.12% of respondents who had high digital literacy in online media also had a household life that was quite harmonious, far from the various categories that caused the phenomenon of domestic violence.